2012
DOI: 10.3724/sp.j.1227.2012.00411
|View full text |Cite
|
Sign up to set email alerts
|

Carbon sequestration in the total and light fraction soil organic matter along a chronosequence in grazing exclosures in a semiarid degraded sandy site in China

Abstract: Horqin Sandy Land is a fragile, seriously desertified region located in Inner Mongolia of China. Overgrazing is one of the primary drivers of desertification in this region. We investigated whether the establishment of grazing exclosures in areas with active sand dunes enhances soil carbon (C) sequestration and benefits soil recovery. The results showed that soil organic C storage was 1.4, 1.9, and 3.5 times, and light fraction C storage was 2.3, 3.2, and 4.4 times in the 100-cm topsoil after 7, 12, and 25 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…In contrast to our expectation and the results of previous studies conducted in Ethiopia and similar environments (Mekuria et al, 2011;Chen et al, 2012;Nianpeng et al, 2012), the results of the present study did not show a clear trend in some soil properties (e.g, CEC and soil moisture) and SOM with exclosure age (Tables III and IV; Figure 2). This could indicate that the influence of exclosure age on soil properties and SOM is moderated by other factors related to management.…”
Section: Sitescontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to our expectation and the results of previous studies conducted in Ethiopia and similar environments (Mekuria et al, 2011;Chen et al, 2012;Nianpeng et al, 2012), the results of the present study did not show a clear trend in some soil properties (e.g, CEC and soil moisture) and SOM with exclosure age (Tables III and IV; Figure 2). This could indicate that the influence of exclosure age on soil properties and SOM is moderated by other factors related to management.…”
Section: Sitescontrasting
confidence: 99%
“…Chen et al . () suggested that exclosures have the capacity to increase soil C sequestration; however, decades will be required to detect the change in soil C. Reeder et al . () emphasize the importance of semiarid and arid ecosystems of including inorganic C in evaluating the impacts of exclosures on soil C, as long‐term studies required to detect change in SOC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Restoration of sandy land is critical for the development of local economy and ecology. During the process of sandy land restoration from mobile dune to sandy grassland, soil physical and chemical properties vary greatly (Li et al, 2006;Chen et al, 2012), which also is true for vegetation characteristics such as vegetation cover, species richness etc. (Zuo et al, 2012a).…”
mentioning
confidence: 99%
“…Thus, changes in the total SOC contents due to the agricultural management occur slowly due to the high background C in soil (Blair et al, 1995). However, labile fractions tend to respond faster to the crop management changes and by driving crucial soil processes, such as nutrient cycling and biological activity, these fractions can significantly influence the quality of an agricultural land (Chen et al, 2012;Duval et al, 2013).…”
Section: Introductionmentioning
confidence: 99%